PENGGUNAAN MEDIA KARTU HURUF DALAM MENINGKATKAN KEMAMPUAN MENGENAL HURUF PADA ANAK USIA 5-6 TAHUN DI RA JANNAH AL RAYYAN KOTA PADANGSIDIMPUAN - Aisat Mikyal; Nur syaidah; Dina Khairiah (STKIP Subang, 2026)
This research is motivated by the low ability to recognize letters in children aged 5-6 years at RA Jannah AL Rayyan Padangsisimpuan City identified in the initial observation where most children still have difficulty in recognizing, distinguishing and naming all letters of the alphabet. This study aims to describe the process of implementing letter card media and prove the increase in the ability to recognize letters in children aged 5-6 years after the application of the letter card media. This study uses the Classroom Action Research (CAR) method which is carried out in two cycles, where each cycle consists of four stages: planning, action, observation, and reflection. The subjects of this study were 15 children in group B (aged 5-6 years). Data were collected through observation and documentation. The results showed an initial interest from the children although most of them still stuck letters to the board randomly and had not shown any developing recognition of letters after the action was carried out. The results obtained from cycle I meeting 1 component percentage was 37% with the category of MB (Starting to Develop) development achievement. The results obtained from cycle I of meeting 2 components showed that the percentage was 56.1% with the BSH (Developing According to Expectations) development achievement category having an average percentage of 46.7% with the MB (Starting to Develop) development achievement category. The highest increase occurred in Cycle II, where the average ability to recognize letters. This encourages children to develop children's confidence in the results of courage in recognizing letters in front of teachers and friends. The results obtained from cycle II meeting 1 component percentage as much as 81.6% with the category of development achievement BSB (Developing Very Well) data obtained from cycle II meeting 2 component percentage as much as 94.4% with the category of development achievement BSB (Developing Very Well) has an average percentage of 88% with the category of development achievement BSB (Developing Very Well). Children's development is developing very well, children show an increase in recognizing real letters, both in terms of cognitive / literacy, language (vocabulary), and psychomotor (Physical Skills). This increase shows that the use of letter card media is effective because it is able to create a more interactive, interesting, and concrete learning atmosphere, thereby increasing children's interest in recognizing letters and understanding of all letters of the alphabet.